Artichoke Leaf Extract-Mediated Neuroprotection against Effects of Aflatoxin in Male Rats. (19th July 2022) - Ibrahim, Enas A.; Yousef, Mokhtar I.; Ghareeb, Doaa A.; Augustyniak, Maria; Giesy, John P.; Aboul-soud, Mourad A. M.; El Wakil, Abeer
Abstract : Attenuation of adverse effects of aflatoxin (AFB1 ) in brains of B1 rats by extracts of leaves of artichoke was studied. The active ingredients in extracts of leaves of artichoke, Cynara scolymus L., were determined by HPLC analysis. In the 42-day experiment, rats were exposed to either sterile water, 4% DMSO, 100 mg artichoke leaf extract/kg body mass, 72  μ g aflatoxin B1 /kg body mass, or AFB1 plus artichoke leaf extract. Neurotoxicity of AFB1 was determined by an increase in profile of lipids, augmentation of plasmatic glucose and concentrations of insulin, oxidative stress, increased activities of cholinergic enzymes, and a decrease in activities of several antioxidant enzymes and pathological changes in brain tissue. Extracts of artichoke leaf significantly reduced adverse effects caused by AFB1, rescuing most of the parameters to values similar to unexposed controls, which demonstrated that adverse, neurotoxic effects caused by aflatoxin B1 could be significantly reduced by simultaneous dietary supplementation with artichoke leaf extract, which itself is not toxic.